The abolition of immigration restrictions and the performance of firms and workers: Evidence from Switzerland - Andreas Beerli; Jan Ruffner; Michael Siegenthaler; Giovanni Peri (ETH Zurich, KOF Swiss Economic Institute, 2020)
We study a reform that granted European cross-border workers free access to the Swiss labor market and had a stronger effect on regions close to the border. The greater availability of cross-border workers increased foreign employment substantially. Although many cross-border workers were highly educated, wages of highly educated natives increased. The reason is a simultaneous increase in labor demand: the reform increased the size, productivity, and innovation performance of skill-intensive incumbent firms and attracted new firms, creating opportunities for natives to pursue managerial jobs. These effects are mainly driven by firms that reported skill shortages before the reform.
hdl:20.500.11850/432769
Keywords: F22; J22; J24; J61; 330; border region; cross-border workers; free movement of persons; firm performance; firm relocation; immigration policy; immigration restrictions; labor mobility; skilled immigration